2022
DOI: 10.1021/acsami.1c23431
|View full text |Cite
|
Sign up to set email alerts
|

Deep Elastic Strain Engineering of 2D Materials and Their Twisted Bilayers

Abstract: Conventionally, tuning materials’ properties can be done through strategies such as alloying, doping, defect engineering, and phase engineering, while in fact mechanical straining can be another effective approach. In particular, elastic strain engineering (ESE), unlike conventional strain engineering mainly based on epitaxial growth, allows for continuous and reversible modulation of material properties by mechanical loading/unloading. The exceptional intrinsic mechanical properties (including elasticity and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 80 publications
0
14
0
Order By: Relevance
“…Experimentally, interlayer twist [ 175 ] and strain engineering [ 33 ] have been adopted to modulate the physical properties of 2D materials, the combination of these two strategies will allow great potential to the systematic control of not only their electronic and optoelectronic behavior, [ 176 ] but also their mechanical properties. For example, it has been reported that the elastic Young's modulus and breaking strength of 2D materials are closely related to the interlayer sliding, [ 177 ] and the introduction of interlayer twist may provide an efficient knob to modulate these mechanical properties.…”
Section: Discussionmentioning
confidence: 99%
“…Experimentally, interlayer twist [ 175 ] and strain engineering [ 33 ] have been adopted to modulate the physical properties of 2D materials, the combination of these two strategies will allow great potential to the systematic control of not only their electronic and optoelectronic behavior, [ 176 ] but also their mechanical properties. For example, it has been reported that the elastic Young's modulus and breaking strength of 2D materials are closely related to the interlayer sliding, [ 177 ] and the introduction of interlayer twist may provide an efficient knob to modulate these mechanical properties.…”
Section: Discussionmentioning
confidence: 99%
“…Strain engineering has been reported as a favorable approach to modulating the electronic properties of Janus monolayers. 49,50 It is noted that the electronic characteristics of 2D layered-structures are particularly sensitive to structural fluctuations. The crystal structure, including the chemical bond lengths between atoms, is changed when strain is applied, leading to a significant change in the hopping energy.…”
Section: Electronic Propertiesmentioning
confidence: 99%
“…It may reach the strain state with high magnitude even beyond the theoretical strength and allow continuous and reversible modulation of electronic and mechanical properties. 27,28 For example, a reversible strain of 15% was achieved in nanowires of silicon. 29 An unprecedented reversible ferroelastic strain of 73.2% was reported in 2D honeycomb monolayers, including the Janus VSSe monolayer, 30 BN and stanene.…”
Section: Introductionmentioning
confidence: 99%